Analyzing Climate Change Status through Evaluating Trend of Temperature and Rainfall and Predicting Future Climate Change Status at Lake Tana Basin - Zeleke, Tesfaye Bayu; Soeprobowati, Tri Retnaningsih; Adissu, Solomon; Abatechanie, Meseret (Applied Environmental Research, 2024)
The trends of temperature and rainfall are critical indicators of climate change within a certain area. However, the existence of climate change is not locally understood in most parts of the world. This research aims to analyze the trend of temperature and rainfall in the Lake Tana Sub-basin as a means to understand the current and future status of climate change. The trends of temperature and rainfall were analyzed using the modified Mann-Kendall trend test, while the autoregressive integrated moving average model (ARIMA) was used to predict future temperature and rainfall. The findings reveal that monthly temperatures show a significant increasing trend for March, April, May, June, and December with Z-values of 3.96, 3.32, 2.64, 3.21, and 4.6, respectively. Seasonal and annual temperatures also show a significant increasing trend with Z-values of 4, 5.35, 5.08, and 4.41 for spring, autumn, winter, and annual, respectively. The Mann-Kendall trend analysis results show that monthly, seasonal and annual rainfall exhibit significant increasing trends for some months and seasons. The results of the ARIMA model suggest that the predicted values of temperature and rainfall will continue to increase over the next 10 years in the study area. Based on these findings, it can be concluded that there is a significant and increasing trend in temperature and rainfall, which will likely continue over the next decade, indicating the presence of climate change in the study area. The research findings suggest that temperature and rainfall have been increasing over time, leading to climate change in the study area, so sustainable lake management and urban development should be practiced to mitigate and adopt climate change.